The Influence of Conditions of Secondary Propylene Recycling in the Presence of Vegetable Fillers on Thermal Properties of Polymer Composites - Borisovich Glazyrin, Andrei; Viktorovna Bazunova, Marina; Petrovich Zakharov, Vadim; Mikhailovna Zakharova, Elena (International Journal of Engineering and Technology, 2018)
This article discusses the influence of conditions of secondary polypropylene recycling in the presence of vegetable fillers on thermal properties of polymer composites. Secondary polypropylene was recycled by the following methods: extrusion using two-screw extruder, agitation in mixing chamber of laboratory station (plastograph), die casting. Polymer composites on the basis of secondary polypropylene in the presence of vegetable fillers (wood dust, rice hulls, buckwheat hulls, and chaff) were produced by extrusion. Thermal properties of polymer composites were determined by thermogravimetric analysis and differential scanning calorimetry. It is established that recycling of secondary polypropylene by various methods does not change melting and crystallization points of polymer phase but is accompanied with decrease in melting enthalpy (by 9-11%) and crystallinity (by 5.6-6.5 %). The polypropylene samples obtained by recycling are characterized by lower thermal stability in air in comparison with initial polypropylene. Addition of vegetable filler to polymer composite on the basis of secondary polypropylene significantly decreases (by 1.13-1.48 times) melting enthalpy and crystallization of polymer phase. The compounds are characterized by relatively high thermal stability: their initial destruction points are close to parameters of initial polymer.Â Â